The Influence of Authentic Leadership On Employee Performance Through Employee Involvement In Lawu Tirta Regional Public Water Companies, Magetan District - Yustiarini, Yeny; Kistyanto, Anang; Tri Wijayati Wardoyo, Dewie (Journal of Business Management Education (JBME), 2024)
This research aims to examine the influence of authentic leadership on the performance and examine the mediating role of employee engagement on employee performance of employees of the Lawu Tirta Regional Public Water Company, Magetan Regency. This research uses a quantitative approach with Partial Least Squares structural equation modeling (PLS- SEM) to predict and confirm the given hypothesis. This research uses a Google form to collect data on employees of the Lawu Tirta Regional Public Water Company, Magetan Regency. Respondents in this study were 114 respondents. The research results show that authentic leadership has a positive and significant influence on employee engagement. Furthermore, authentic leadership has a significant positive influence on employee performance. Employee engagement has a significant influence on employee performance. And authentic leadership has a positive and significant effect indirectly through employee involvement on employee performance at the Lawu Tirta Regional Drinking Water Company, Magetan Regency.